(untitled) - Drosopoulos, Sakis (Boca Raton, 2006)
Divided into two major sections, this groundbreaking text starts with a general introduction to insect sounds and communication that leads into a discussion of the technical aspects of recording and analyzing sounds. It then considers the functioning of the sense organs and sensory systems involved in acoustic behavior, and goes on to investigate the impact that variables such as body size and temperature have on insect sounds and vibrations. Several chapters are devoted to various evolutionary and ecological aspects of insect communication, and include rare information on seldom-studied groups, including Neuropterida and Plecoptera. The second section of the book includes chapters on communication and song repertoires of a wide diversity of insects, including Heteroptera, Auchenorrhyncha, Psylloidea, Diptera, Coleoptera, and Hymenoptera . Insect Sounds and Communication is packaged with a DVD, which holds sound and video recordings of many of the insects discussed throughout the text, as well as many full color illustrations not included in the printed text. The DVD also features an unabridged discussion in French of the contribution of the famous French cicadologist, Michel Boulard.
Keywords: Insect sounds,Sound production by insects,Animal communication